Syrian episodes sons, fathers, and an anthropologist in Aleppo - Borneman, John 1952- (Princeton University Press, 2007)
When Princeton anthropologist John Borneman arrived in Syria's second-largest city in 2004 as a visiting Fulbright professor, he took up residence in what many consider a "rogue state" on the frontline of a "clash of civilizations" between the Orient and the West. Hoping to understand intimate interactions of religious, political, and familial authority in this secular republic, Borneman spent much time among different men, observing and becoming part of their everyday lives. Syrian Episodes is the striking result